1978
DOI: 10.1210/endo-103-6-1992
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,25-Dihydroxyvitamin D in the Nephrectomized Pregnant Rat*

Abstract: Pregnant rats were maintained on diets either adequate or deficient in vitamin D. On the 20th day of gestation, animals were either nephrectomized bilaterally or sham operated. Immediately therafter, four groups of nephrectomized or sham-operated pregnant rats received iv [26,27-3H]25-hydroxyvitamin D3 ([26,27-3H]25OHD3), while two groups received [1,2-3H,4-14C]D3. The animals were sacrificed 10-24 h later. The distribution of the radiolabeled metabolites of vitamin D3 was determined in extracts of maternal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 11 publications
3
44
0
1
Order By: Relevance
“…The basic experiment of Fraser and Kodicek was responsible for the concept that the kidney is the sole site of production of 1,25-(OH)2D3, and, in fact, this remains true for all animals except pregnant females. Weisman et al (6) reported that anephric, pregnant female rats could biosynthesize a compound that appeared to be 1,25-(OH)2D3. Similar experiments by Gray et al (7) provided even stronger evidence that pregnant, anephric female rats were capable of producing 1,25-(OH)2D3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The basic experiment of Fraser and Kodicek was responsible for the concept that the kidney is the sole site of production of 1,25-(OH)2D3, and, in fact, this remains true for all animals except pregnant females. Weisman et al (6) reported that anephric, pregnant female rats could biosynthesize a compound that appeared to be 1,25-(OH)2D3. Similar experiments by Gray et al (7) provided even stronger evidence that pregnant, anephric female rats were capable of producing 1,25-(OH)2D3.…”
mentioning
confidence: 99%
“…Gray et al (7) also provided evidence that a possible site of biosynthesis is the placenta. Recently we have developed methods for measuring mammalian 25-OH-D3-la-hydroxylase activity and, therefore, proceeded to test directly the hypothesis put forth by Weisman et al (6) and by Gray et al (7).…”
mentioning
confidence: 99%
“…4). Following the reports of Weisman et al [5], Gray et al [6], and Tanaka et al [7], kidney is no longer considered to be the sole site of 25-(OH)D,-1 a-hydroxylation during pregnancy. Several studies have reported that the term human feto-placental unit can produce 1,25-(OH),D, [8-131.…”
Section: Resultsmentioning
confidence: 99%
“…This concept is based on experimental results showing that 1,25-(OH)*D3 is no longer formed after bilateral nephrectomy [l]. However, this is clearly not the case during pregnancy, as rat maternal blood contains 1,25-(OH),D, even after experimental bilateral nephrectomy [5,6], and as foeto-placental tissues from both animals and humans synthesize 1,25-(OH),D, in vitro [7-131. Studies on the ability of the human uterine cells to synthesize 1,25-(OH),D, have so far been mostly limited to the late pregnancy period [g-13], and/or have involved incubations with whole tissue homogenates [8,9,12,13]. The location and characterization of the cells responsible for the 1,25-(OH),D, synthesis in the feto-placental unit at this time of pregnancy remains a fertile field for debate [8-131.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D regulates serum calcium (Ca) and phosphate (Pi) levels through stimulation of intestinal transport and through mobilization of bone mineral. However, there is still controversy about which role vitamin D plays in regulating Ca and P1 homeostasis during pregnancy (Weisman, Vargas, Duckett, Reiter & Root, 1978; Gray, Lester & Lorenc, 1979;Halloran & DeLuca, 1979). In addition to being transported across the intestinal mucosa, Ca and Pi have to be transported across the placenta during pregnancy to provide adequate supply to the fetus and to ensure fetal Ca and Pi homeostasis.…”
Section: Introductionmentioning
confidence: 99%